Evaluación del efecto de Metarhizium anisopliae de tres productos comerciales y dos frecuencias de aplicación para el control de salivazo en el cultivo de caña de azúcar (Saccharum officinarum L.) parroquia Palo Quemado, cantón Sigchos, provincia Cotopaxi. - Moreno Faconda, Sergio Fabian (2023)
The research was conducted at Palo Quemado parish, Sigchos, Cotopaxi, with the objective to evaluate Metarhizium anisopliae effect on three commercial products with two application frequencies for spittlebug control about sugarcane (Saccharum officinarum L.). A factorial arrangement (3 * 2) + 1 was implemented, in a completely randomized block design (DBCA) with 4 replications, resulting in 28 experimental units, a total area of 7140 m2. Three commercial products were used, (EFICAX, SOLUBIOMIX, BIOMRTARHIZIUM) with a concentration of (5ml/l) with 2 and 3 applications (every 15 days) on the crop. It was determined that the best treatment based on the 3 applications was (EFICAX) with its active ingredients Beauveria bassiana, Metarhizium anisopliae, Lecanicillum lecanii, Purpureocillium, in the variables; plant height at (56 days), with a plant height (1.44 m), insect mortality (100%) on three applications, plant health at (90%), according to the application cost of product is (EFICAX) with a cost of $ 77 presented at research time at pest control. This technology will allow farmers to control Salivazo pest (Mahanarva andigena) in a biological way without environment al damage with a cleaner organic production of sugar cane, since obtained results the quality and production will improve.